Systematic Review of the Efficacy of Particulate Versus Nonparticulate Corticosteroids in Epidural Injections. Issue 5 (30th November 2016) - Mehta, Priyesh; Syrop, Isaac; Singh, Jaspal Ricky; Kirschner, Jonathan
Abstract : Objective: To systematically analyze published studies in regard to the comparative efficacy of particulate versus nonparticulate corticosteroids for cervical and lumbosacral epidural steroid injections (ESI) in reducing pain and improving function. Type: Systematic review. Literature Survey: MEDLINE (Ovid), EMBASE, and Cochrane databases were searched from the period of 1950 to December 2015. Methodology: Criteria for inclusion in this review were (1) randomized controlled trials and (2) retrospective studies that compared particulate versus nonparticulate medication in fluoroscopically guided injections via a transforaminal (TF) or interlaminar (IL) approach. Each study was assigned a level of evidence (I‐V) based on criteria for therapeutic studies. A grade of recommendation (A, B, C, or I) was assigned to each statement. Categorical analysis of the data was reported when available, with success defined by the minimal clinically important difference for appendicular radicular pain—a reduction of at least 2 on the visual analog scale. When data were available, additional categorical analysis included the proportion of individuals with a reduction in pain of at least 50%, 70%, or 75%. Follow‐up was included at all reported intervals from 2 weeks to 6 months. Synthesis: Three cervical ESI and 6 lumbar ESI studies were found to be suitable for review. Of the 3 cervical ESI studies, 2 were retrospective studies with grade III level of evidence and 1 was a randomized controlled trial with grade II evidence. Of 4 lumbar ESI studies that used a TF approach, the 2 randomized double‐blinded controlled trials were grade I evidence and 2 retrospective studies were grade II and III level of evidence. One randomized controlled trial using the lumbar IL approach was level II evidence. One retrospective cohort study using the lumbar TF, IL and caudal approach was level III evidence. Conclusions: There is no statistically significant difference in terms of pain reduction or improved functional outcome between particulate and nonparticulate preparations in cervical ESI and, therefore, the authors recommend using nonparticulate steroid when performing cervical TFESI (Grade of Recommendation: B). In patients with lumbar radiculopathy due to stenosis or disk herniation, TFESI using particulate versus non‐particulate is equivocal in reducing pain (Grade of Recommendation: B) and improving function (Grade of Recommendation: C) and therefore the authors recommend the use of nonparticulate steroids for lumbar TFESI in patients with lumbar radicular pain (Grade of Recommendation: B). There is insufficient information to make a recommendation of one steroid preparation over the other in lumbar ILESI (Grade of Recommendation: I). Given the lack of strong data favoring the efficacy of one steroid preparation over the other, and the potential risk of catastrophic complications, all of which have been reported with particulate steroids, nonparticulate steroids should be considered as first line agents when performing ESIs. Level of Evidence: III